Приключения Незнайки и его друзей - Носов Николай Николаевич (Эксмо, 2018)
Экземпляры: СБ (20190131) / Инвентарный номер: 56982 / Цена: 482.00 / Сис.шифр: Р2ср / Авт.знак: Н 84 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6